Turn on thread page Beta
    • Thread Starter
    Offline

    1
    ReputationRep:
    ok im stuck on the last part of this question
    (ref: Heineman P1, pg 98, q46):
    m => 2x + 3y = 15
    the point P lies on m and has x co-ordinate = -3
    therefore P(-3,7).
    the points A(1,0) and B(5,6) lie on the line => y = (3/2)x - 3/2.
    [q] show that PA = PB.

    thanks in advance: adam.
    Offline

    14
    ReputationRep:
    √(3²+6²) = √45 = PA
    √(8²+1²) = √65 = PB

    I think the question is wrong. They obviously have different directions and by pythagoras it's clear they have different lengths.
    • Thread Starter
    Offline

    1
    ReputationRep:
    ok, what are you doing there to find PA and PB i dont understand :x

    edit: nm.
    Offline

    2
    ReputationRep:
    P(-3,7)
    A(1,0)
    B(5,6)

    using,
    len=sqrt((x1-x2)^2 + (y1-y2)^2)

    PA=sqrt((-3-1)^2 + (7-0)^2)=sqrt(16+49)=sqrt(65)
    PB=sqrt((-3-5)^2 + (7-6)^2)=sqrt(64+1)=sqrt(65)

    hence PA=PB
    Offline

    14
    ReputationRep:
    (Original post by Fermat)
    P(-3,7)
    A(1,0)
    B(5,6)

    using,
    len=sqrt((x1-x2)^2 + (y1-y2)^2)

    PA=sqrt((-3-1)^2 + (7-0)^2)=sqrt(16+49)=sqrt(65)
    PB=sqrt((-3-5)^2 + (7-6)^2)=sqrt(64+1)=sqrt(65)

    hence PA=PB
    behold fermat, mathematical genius.

    hows the theorem going?
 
 
 
Poll
Favourite type of bread

The Student Room, Get Revising and Marked by Teachers are trading names of The Student Room Group Ltd.

Register Number: 04666380 (England and Wales), VAT No. 806 8067 22 Registered Office: International House, Queens Road, Brighton, BN1 3XE

Write a reply...
Reply
Hide
Reputation gems: You get these gems as you gain rep from other members for making good contributions and giving helpful advice.